(untitled) (Academia Journal of Medicine, 2019)
Rheumatic heart disease (RHD) is the most serious manifestations of rheumatic fever, which is caused by group A Streptococcus (GAS or Streptococcus pyogenes) infection. RHD is an auto immune sequelae of GAS pharyngitis, rather than the direct bacterial infection of the heart, which leads to chronic heart valve damage. Although antibiotics like penicillin are effective against GAS infection, improper medical care such as poor patient compliance, overcrowding, poverty, and repeated exposure to GAS, leads to acute rheumatic fever and RHD. Thus, effort to design a vaccine based on emm gene identification of GAS, M-protein going on for more than 40 years, is unlikely to succeed. M-protein is strain specific. Infection with one strain does not provide immunity from infection with another strain. Based on the emm gene identification, of 250 or more identified strains of GAS, the distribution is heterogenous and keeps changing. The M-protein gene sequence of the organism tends to mutate. A vaccine prepared from available strains may not be effective against a strain following mutation.